Analisis Penerapan Akuntansi Pada Usaha Mikro Kecil dan Menengah (UMKM) Studi Kasus pada Warung Kopi Mbah Kuwot di Trenggalek - Pradana, Rahardyan Sriatma; Junaidi, Junaidi; Mawardi, M. Cholid (Universitas Islam Malang, 2024)
Micro, Small and Medium Enterprises (MSMEs) have a very important role for economic development in Indonesia. MSMEs are the largest contributor of income to the country. MSMEs are one of the driving sectors of the economy in Indonesia and a vehicle for job creation. Financial records are very important for a business unit, including for MSMEs. Financial records for MSMEs not only present good and neat financial reports, but also make it easier to plan funding and to see the effectiveness and efficiency of the business. Based on the formulation of the problem, this research was carried out with the aim of determining the application of accounting records in MSMEs of Warung Kopi Mbah Kuwot located on Jl. Pangeran Diponegoro No. 80, Sawahan, Sumbergedong, Trenggalek District, Trenggalek Regency. This study uses qualitative research methods. The data collection was carried out by means of interviews, direct observation at the research site and documentation through the collection of documents from the cash inflow and cash outgoing record books. The results of the study show that the recording of financial statements carried out by MSME actors is still simple and does not have a good financial statement recording system according to the Financial Accounting Standards (SAK). This research needs to be developed so that the recording of business financial statements can be presented better through the analysis of financial statements based on SAK EMKM.Keywords: Micro, small and medium enterprises (MSMEs), financial recording, financial accounting standards (SAK), SAK EMKM.